PeopleSoft for the Oracle DBA - Kurtz, David (Apress, 2012)
PeopleSoft for the Oracle DBA, Second Edition stands on the boundary between the PeopleSoft application and the Oracle database. This new edition of David Kurtz's book is freshly revised, showing how to tame the beast and manage Oracle successfully in a PeopleSoft environment. Youll learn about PeopleSofts Internet architecture and its use of Oracles Tuxedo Application Server. Youll find full coverage of key database issues such as indexing, connectivity, and tablespace usage as they apply to PeopleSoft. Kurtz also provides some of the best advice and information to be found anywhere on managing and troubleshooting performance issues in a PeopleSoft environment. The solid coverage of performance troubleshooting is enough by itself to make PeopleSoft for the Oracle DBA a must-have book for any Oracle Database administrator working in support of a PeopleSoft environment. Explains PeopleSofts technical architecture as it relates to Oracle Database Demonstrates how to instrument and measure the performance of PeopleSoft Provides techniques to troubleshoot and resolve performance problems